Exploring the Local Potential of Marine Ecotourism in Sabang Island as a Contextual-Based Resource for Biology Learning - Noviyanti, Anita; Ismulyati, Sri; Febriyanti, Dewi; Aswita, Dian (Biotik, 2025)
This study aims to analyze and reconstruct the local potential of natural resources in the Iboih ecotourism areas as a source of biology learning. The final target of this study is to be used as references for educators and developers of biology learning in utilize local potential as a context for biology learning. The method used by this study is descriptive research with a qualitative approach. This study was conducted in the Iboih ecotourism areas of Sabang Island, consists of two stages, namely the first exploration of local potential in the ecotourism area, and the second describing local potential as a source of learning based on contextual. Data analysis was carried out using descriptive analysis techniques by using observation sheet that researcher developed. The results of observations and analysis showed that the material that can be used as a source of learning from the Iboih ecotourism areas is related to ecology, with material content about ecosystems, biodiversity, and ecological interactions. Therefore, the study of local potential in the Iboih ecotourism areas is known potential to be used as a source of contextual biology learning, that closely related to eveyday life.